Analisis Multilevel pada NEET di Wilayah Perdesaan Indonesia Tahun 2022 - Jessica, Theresia Intan; Arcana, I Made (Seminar Nasional Official Statistics, 2024)
The population aged 15-24 years has played an important role in achieving Indonesia Emas 2045 and needs to be improved through education, employment, and training. Not in Education, Employment, or Training (NEET) is an indicator that counts those who are not in education, employment or training. In the last 4 years, the highest percentage of NEETs was in rural areas, especially in 2022. This research aims to analyze the variables that affect NEETs using multilevel binary logistic regression seen from individual and household factors. The results of the study showed that 23.6 percent of the 15-24 year-olds in the Indonesian countryside are NEETs. Individual factors that influence are gender, disability, age, marital status, education, training experience, and work/employment experience. The education of the head of the household, the working status of the household, and the number of household members are the variables that affect the NEET based on household factors. It is hoped that this research will reduce the percentage of NEETs in the Indonesian countryside and improve the quality of the population towards Indonesia Emas 2045.